Protocolo para digitalização e modelagem de cafeeiro para fins de simulação numérica - Carvalho, Enio de Araújo (2016)
The objective of this work was to develop a three-dimensional computer model of a coffee plant (Coffea Arabia L.) and conduct numerical simulation experimental tests via Finite Element Method (FEM). The project was developed based on the three-dimensional computer model of a coffee tree, applying computer modeling and numerical simulations. To this end, we obtained a three-dimensional computer model representative of the morphological structure of structure of an adult coffee plant. Subsequently, we scanned the wood structure sustaining leaves and fruits, formed by the main, or orthotropic, trunk and plagiotropic ramifications of a coffee plant of cultivar Catuaí Vermelho IAC 144, with eight years of age, sampled from a rural property located in the municipality of Nepomuceno, Minas Gerais, Brazil. As main result of this research, a protocol for digitalization and modeling of coffee plants was developed for numeric simulation via FEM. This work can contribute in directing new scientific researches for this area and in developing new technologies for mechanical harvest systems, directly benefiting the industrial sector and the agricultural medium.